The Effect of Using Cake and ELSA Speak Application on Students’ Pronunciation Skills at the Eighth Grade of SMP Negeri 25 Medan - Masda Saragih; Kammer Sipayung; Lastri W. Manurung (UIBU, 2023)
The CAKE application is an English learning application that functions to increase student learning activities in the field of English. Meanwhile, ELSA Speak, an 'Education Tech' startup based in Silicon Valley, United States, uses speech recognition technology and Artificial Intelligence to help students improve their English-speaking skills. The objective of this research is to determine the effect of using CAKE and ELSA Speak on students’ pronunciation skills in the eighth grade at SMP Negeri 25 Medan. The method used in this research is quantitative approach with data collection stages, namely pre-test and post-test, and then the data that has been obtained is analyzed using the SPSS application. Based on the data analysis, the researcher found that the iELSA iSpeak iApplication can improve students’ pronunciation skills. This research shows that there are several problems experienced by junior high school students in learning pronunciation skills. Therefore, this research aims to describe the problem of speaking ability in junior high school and the students'' learning difficulties in current pronunciation skills. As a result of the pre-test and post-test, the mean scores, which were given, were i64,83 and i91,38. The students who were taught using CAKE and ELSA iSpeak and the students who were taught using the traditional method exhibited significantly different levels of achievement. The statistics also revealed that students believed that pronunciation could be improved by using instructional material. The majority of them also mentioned that they included educational media into their regular discourse